Effect of some factors on growth of lambs from crossing between the Improved Wallachian and East Friesian - Kuchtík, J.; Dobeš, I. (Czech Journal of Animal Science, 2006)
The effect of some factors (genotype, sex, litter size, age of dam at lambing, month of lambing and year of birth of lamb) on the growth of lambs - crossbreds between the Improved Wallachian (IW) and East Friesian (EF) breed was evaluated in operating conditions during two successive years. Three genotypes were evaluated: IW 50 EF 50, EF 75 IW 25 and EF 87.5 IW 12.5. The evaluation of the effect of genotype on growth showed that this factor did not have a significant effect on the majority of growth traits under study. In the period from birth to 100 days of age the highest daily gain was found in IW 50 EF 50 (263 g). The daily gains of EF 75 IW 25 and EF 87.5 IW 12.5 in this period were lower but identical (244 g). Age of dam had a significant effect on the majority of growth traits under study. Sex of lamb had a significant effect on body weight at 100 days of age and also on the majority of daily gains under study. The factors litter size, month of lambing and year of lamb birth were the most significant sources of variation of daily gains. As far as the non-genetic factors were concerned, the highest daily gains from birth to 100 days of age were recorded in males (259 g), in singles (260 g), in lambs from 4-years-old ewes (269 g), in lambs born in January (263 g) and in lambs born in the first year of evaluation (256 g). The analysis of phenotypic correlations indicated that body weight at birth showed a positive and highly significant (P ≤ 0.01) effect on the majority of growth traits under study. All phenotypic correlations between individual body weights were positive and high (P ≤ 0.01). The majority of phenotypic correlations between individual daily gains under study were also positive and high (P ≤ 0.01).
Keywords: lamb; growth traits; Improved Wallachian; East Friesian